1968
DOI: 10.1161/01.cir.37.1.36
|View full text |Cite
|
Sign up to set email alerts
|

Observations on the Blood Pressure of Tibetans

Abstract: Observations on the blood pressure of a group of 660 displaced male Tibetans revealed striking dissimilarities in regard to the mean systolic and diastolic figures as compared to those reported for Europeans and Americans. The average Tibetan figures are lower than those of Western populations; however, a comparable variability after the fourth decade and a parallel spread of values with age and weight were found in the Tibetan data. The socioeconomic status and height bore no relation to the blood pressure le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

1970
1970
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Although the present study's finding of multivariate adjusted associations between BP and age, alcohol intake, and urban lifestyle is consistent with past research the inverse relationship between self-reported daily salt consumption and BP is not 22,23 . High consumption of salt as a traditional dietary habit has been identified as one of the key factors for high BP in HA Tibetan populations 24,25 . The method used in the present study of self-report to calculate salt consumption could have systematically led to underestimation of salt intake in those with the highest salt intake.…”
Section: Discussionmentioning
confidence: 99%
“…Although the present study's finding of multivariate adjusted associations between BP and age, alcohol intake, and urban lifestyle is consistent with past research the inverse relationship between self-reported daily salt consumption and BP is not 22,23 . High consumption of salt as a traditional dietary habit has been identified as one of the key factors for high BP in HA Tibetan populations 24,25 . The method used in the present study of self-report to calculate salt consumption could have systematically led to underestimation of salt intake in those with the highest salt intake.…”
Section: Discussionmentioning
confidence: 99%
“…Living separately from other ethnic populations, minorities thus provide an ideal genetically homogeneous population to investigate the contribution of hereditary factors to specific disease. Given the fact that Tibetans have high dietary salt intake [Sehgal et al, ], we decided to study the genetic influence of the water‐sodium metabolism pathway on Tibetan hypertension, rather than the presumably activated RAS system on high‐altitude circumstance [Parati et al, ] .…”
Section: Discussionmentioning
confidence: 99%
“…Tibetans have been reported to consume ‘traditional salty butter tea’ whose salt content is four to five times the amount recommended by the WHO. 7 46 Indeed, the result of a recent study showed that a low-sodium, high-potassium salt-substitute intervention caused a dramatic fall in BP in hypertensive Tibetans. 47 …”
Section: Discussionmentioning
confidence: 99%